DEVELOPMENT TRENDS FOR ROLLING STOCK TRACTION MOTORS - O.V. Pasko (National Technical University "Kharkiv Polytechnic Institute", 2013)
Rolling stock on the railways of Ukraine has not been updated for many years, which has led to significant wear of the country electric and diesel locomotive fleet. A way out of the existing situation is execution of major overhaul with extension of locomotive life to allow their operation for several more years. Repair or upgrading as well as putting new rolling stock into operation must be accompanied by implementation of state-of-the-art traction electric drives.